Awareness and Referral Attitudes of Diabetic Retinopathy among Surgeons at a Tertiary Care Hospital in Pakistan: Doi: 10.36351/pjo.v39i3.1553 - Malik, Muhammad Bilal; Chippa, Shaukat Ali; Rashid, Asma; Akram, Sharmeen (Pakistan Journal of Ophthalmology, 2023)
Purpose: To assess the awareness of diabetic retinopathy (DR) in surgeons and compare their referral practices from different specialities at a tertiary care center. Study Design: Cross sectional survey. Place and Duration of Study: Department of Surgery, Agha Khan University Hospital, Karachi. Methods: A survey was created using Google Forms and the link to the survey was shared to 99 surgery faculty members on official university email addresses. We employed non-probability, convenience sampling technique and the total population of faculty under the Department of Surgery was sampled, including clinical fellows. Residents, research associates, and ophthalmology faculty were subsequently excluded. The survey contained questions in 4 categories; consent, relevant practices of DM, knowledge regarding DR and referral practices to an ophthalmologist. Scoring was based on a 5-point Likert scale with 5 being the most rigorous practice. Data was entered into SPSS v.23. Qualitative data was reported as frequencies with percentages, and quantitative data was reported as mean with standard deviation. Results: Out of 40 participants, 87.5% had excellent practices of diabetes mellitus and 77.5% had excellent knowledge of diabetic retinopathy. Referral practices to an ophthalmologist were graded fair in 75% and poor in 15% whereas, referral practices were fair or poor across all surgical specialties. Conclusion: Our study indicates a gap between knowledge and practices of surgeons regarding DM. Hence, there is a strong need to enhance awareness about timely referrals to an ophthalmologist to prevent complications of diabetes related blindness.